Resource-based enactment and adaptation of workflows from activity diagrams - Bottoni, Paolo; Saporito, Andrea (Electronic Communications of the EASST, 2009)
Workflow management deals with different types of dependencies among tasks, in particular data- and policy-driven. The ability to reason on dependencies of different type allows workflow designers to consider different alternatives, or to define customized flows, reducing non-determinism. We propose a resource-centered view, in which both data-dependency between tasks and plan-dependent ordering of tasks are expressed as production and consumption of resources. This view is translated into a rule-based formalism, expressed in terms of multi-set rewriting for workflow enactment.In turn, rules are themselves seen as resources, so that they are prone to the same rewriting process, in order to redefine process schemas. We show how workflows expressed as activity diagrams can be translated to the proposed formalism, exploiting enforced generative patterns applied to triple graph grammars, and how redefinition of workflow processes can occur through typical patterns of adaptation. We also discuss possible concrete syntaxes for the obtained rules.